Peran Lembaga Pengelola Dana Dan Usaha Keolahragaan (LPDUK) Dalam Pengelolaan Penerimaan Negara Bukan Pajak (PNBP) Untuk Pengembangan Industri Olahraga - Alfisa Triatmoko; Kumba Digdowiseiso (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
The Indonesian government has implemented the Reinventing Government paradigm to improve public services. The paradigm focuses on innovation and adaptability to the changing needs of the population. This article uses a qualitative approach using a literature study. The author tries to explain the concept of rediscovering the role and function of the Sports Fund and Business Management Institution (LPDUK) with BLU status at the Ministry of Youth and Sports in managing Non-Tax State Revenue (PNBP) in the context of developing the sports industry.The role of government in public services includes directing public services, advancing public interests, fostering aspirations, generating potential, coordinating activities, fostering cooperation, and ensuring community welfare. The government is seen as a fixed entity that does not change, but rather adapts to the changing political and technological landscape. The Public Service Agency (BLU) is a key component of this paradigm, combining government and public service functions. BLUs are government agencies that provide public services without requiring government intervention. BLU is also called Non-Tax State Revenue (PNBP) in the APBN structure. Keywords: LPDUK, BLU, PNBP, Ministry of Youth and Sports